PENERAPAN MODEL GROUP INVESTIGASI DENGAN MEDIA FILM UNTUK MENINGKATKAN KESADARAN DAN PRESTASI BELAJAR - Awwalim, Abdul (Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Surabaya, 2015)
This research aimed to see how: The application of Group Investigation Model by movie documenter in raising awareness of State Defense and class XII student achievement IPS SMAN 1 Gedangan. . The research procedure used was Classroom Action Research. This study was conducted in three cycles, each of which consisted of four stages: planning, acting, observing, and reflecting. The research methods employed were observation on the group investigation learning process with movie media, questionnaire of students’ State Defense Awareness and cognitive test to find out the student learning achievement, and interview. The result achieved in this research was as follow. The application of Group Investigation model with documentary movie could also improve the State Defense awareness as indicated by the students’ State Defense awareness values of 64.59 in pre-cycle, increasing to 71.09 in cycle I, 75.28 in cycle II and 78.813 in cycle III, with the classical passing of 96.88% or 31 students. The learning achievement in each cycle also increased significantly from 67.63 in pre-cycle to 73.38 in cycle I, 79.06 in cycle II, and 83.75 in cycle III. The number of students passing the class was 11 in pre-cycle, 17 in cycle I, 21 in cycle II and 29 in cycle III.